Pharmacy Students’ Views on the Inclusion of Immunisation Training in the Pharmacy Curriculum - Nur Aisyah Amiza Mohd Nizam; Norny Syafinaz Ab Rahman; Christopher John Turner; Nor Hidayah Mohd Taufek (Journal of Pharmacy)
Introduction: Immunisation services are usually provided by healthcare workers who receive training in the field of immunisation. In Malaysia, limited exposure of pharmacy students in receiving immunisation training is partly due to lack involvement of pharmacists in immunisation programme. This study aimed to explore the insights of pharmacy students who received introductory training on the role of pharmacist in immunisation and the feasibility of introducing immunisation modules in the pharmacy curriculum.